Integrated weed management on the processing tomato crop and tomato for consumption in natura - Y. O. Castro; S. D. Cavalieri; M. P. Santos; A. Golynski; A. R. Nascimento (Scientific Electronic Archives, 2016)
Weeds cause direct and indirect damage to processing tomato and tomato for consumption in natura. The coexistence period is decisive for the intensity of damage, although the economic cost is also considered for decision making when to control the weeds. There are similarities between processing tomato and tomato for consumption in natura cropping system and peculiarities. This causes the management has adopted its common applications and its variables within each system. As control alternative, the farmer has basically the preventive control, mechanical, cultural, biological and chemical. The application of a single method is not recommended. Ideally, the methods needs to be integrated in order to combat weeds, highly evolved populations and resistant to unfavorable conditions. Consider weed management taking only one control measure is to underestimate the evolutionary ability of such species. Therefore, it is necessary to integrate the various methods available to the weed interference not impede the tomato production.